Implementing a Farmers' Market Incentive Program: Perspectives on the New York City Health Bucks Program - Gayle Holmes Payne, PhD; Holly Wethington, PhD; Lauren Olsho, PhD; Jan Jernigan, PhD; Rosanne Farris, PhD; Deborah Klein Walker, EdD (Centers for Disease Control and Prevention, 2013)
Introduction One strategy for lowering the prevalence of obesity is to increase access to and affordability of fruits and vegetables through farmers' markets. However, little has been documented in the literature on the implementation of such efforts. To address this gap, the Division of Nutrition, Physical Activity, and Obesity (DNPAO) sponsored an evaluation of the New York City Health Bucks program, a farmers' market coupon incentive program intended to increase access to fresh fruits and vegetables in underserved neighborhoods while supporting local farmers. Methods We conducted a process evaluation of Health Bucks program implementation. We interviewed 6 farmer/vendors, 3 market managers, and 4 program administrators, and collected data on site at 86 farmers' markets, including surveys of 81 managers and 141 farmer/vendors on their perspectives on promotion and redemption of the incentive coupons; knowledge and attitudes regarding the program; experiences with markets and products; and facilitators and barriers to program participation. Results Results indicate that respondents view Health Bucks as a positive program model. Farmers' market incentive coupon programs like Health Bucks are one strategy to address the problem of obesity and were associated with higher fruit and vegetable access and purchases in low-income communities. Conclusions This evaluation identified some areas for improving implementation of the Health Bucks program. Farmers' market incentive programs like Health Bucks may be one avenue to increase access to and affordability of fruits and vegetables among low-income persons. Further research is needed to assess the potential effects of these programs on access and health outcomes.